Therapeutic potential of ghrelin/GOAT/GHSR system in gastrointestinal disorders - Ma, Yunxiao; Yan, Qihui; Wang, Ping; Guo, Weiying; Yu, Lu (Frontiers in Nutrition, 2024)
Gastrointestinal (GI) disorders are highly prevalent worldwide. The GI tract, which is the largest endocrine organ, synthesizes a diverse range of hormones and neuropeptides. Ghrelin, a 28-amino-acid peptide, is primarily synthesized by gastric endocrine cells and is currently recognized as the sole peripheral orexigenic hormone.Since its discovery, ghrelin has been extensively studied for its multiple physiological effects, including the stimulation of growth hormone production, gastric acid secretion, GI motility, and food intake. Moreover, ghrelin regulates energy homeostasis, glucose and lipid metabolism, cardiovascular activity, bone formation, fertility, memory, stress, and learning and also exerts inhibitory effects on inflammatory processes. Ghrelin, a peptide primarily secreted in the stomach, acts via the growth hormone secretagogue receptor (GHSR). It regulates several physiological processes, such as feeding behavior, energy homeostasis, glucose and lipid metabolism, cardiovascular function, bone formation, stress response, and learning.GHSR exhibits significant expression within the central nervous system. However, numerous murine studies indicate that ghrelin is limited in its ability to enter the brain from the bloodstream and is primarily confined to specific regions, such as arcuate nucleus (ARC) and median eminence (ME). Nevertheless, the central ghrelin system plays an essential role in regulating feeding behavior. Furthermore, the role of vagal afferent fibers in regulating the functions of ghrelin remains a major topic of discussion among researchers. In recent times, numerous studies have elucidated the substantial therapeutic potential of ghrelin in most gastrointestinal (GI) diseases. This has led to the development of numerous pharmaceutical agents that target the ghrelin system, some of which are currently under examination in clinical trials. Furthermore, ghrelin is speculated to serve as a promising biomarker for GI tumors, which indicates its potential use in tumor grade and stage evaluation. This review presents a summary of recent findings in research conducted on both animals and humans, highlighting the therapeutic properties of ghrelin system in GI disorders.